Motivasi Belajar dan Prokrastinasi Akademik Siswa - Irawan, Muhammad Fery; Budiono, Arifin Nur; Karamoy, Yurike Kinanthy (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
Research on the relationship between learning motivation and academic procrastination in class X students of Madrasah Aliyah Negeri (MAN) 1 Jember for the 2021-2022 academic year involved 205 students out of a total of 432 students who selected by random sampling method. Based on the results of data analysis, it found that students' learning motivation was in the moderate category as much as 52%, while students' academic procrastination was in the moderate category as much as 61%. The results of analysis the Pearson Product Moment correlation show relationship between the two variables. The correlation coefficient is negative (r = -0.477), which indicates a non-unidirectional relationship. The result of comparison of the significant level (p value) is 0.00, which means p value is less than 0.05 (the specified level of significance). Therefore, the alternative hypothesis (Ha) is accepted, which states that is a relationship between learning motivation and students' academic procrastination.